THE IMPACT OF DIGITAL ACCOUNTING ON THE QUALITY OF ACCOUNTING INFORMATION AND ITS REFLECTION IN THE TRANSPARENCY OF FINANCIAL REPORTS - Hadeel Mohammed Noaman; Ihab Hadi Sahib (Scholars Digest Publishing, 2024)
The purpose of this research is to reveal the impact of digital accounting on the quality of accounting information by "efficiency of accounting information, effectiveness of accounting information, credibility of accounting information" and its reflection on the transparency of financial reports among a sample of commercial banks in Najaf, and in order to reach the best results, the research followed the descriptive analytical approach in measuring its variables based on the research problem tagged in (What is the impact of digital accounting on the quality of accounting information and its reflection in the transparency of financial reports at commercial banks?) Based on the questionnaire tool, the (Hassan,2022) scale was adopted to measure digital accounting, (Karsoo,2023) scale to measure the quality of accounting information, and (Hammana & Amiri,2023) scale to measure the transparency of financial reports, and to show the importance of these variables, two packages were used to reach the most accurate results, represented in (SPSS&AMOS. V.28) to determine the extent of integration of these variables and their reflection on the transparency of financial reports, and the research reached several results, foremost of which was that commercial banks in Najaf province focus on providing transparent and credible information by relying on the quality of their accounting information, and this came as a result of efforts, skills and accurate capabilities in digital accounting systems.
Keywords: digital accounting, quality of accounting information, transparency of financial reports.